Effect of COX-2 Inhibitors Selectivity on Lipid Profile in Hyperlipidemic and Normolipidemic Type 2 Diabetics - Najwan K. Fakree; Shatha H. Ali (College of Pharmacy University of Baghdad, 2017)
Development of NSAIDS based on inhibiting cyclooxygenase activity. However, the different physiological consequences arrised by appearance of new drugs with different selectivity to COX-2 enzyme upon their administration with their relevant affects on some cardiovascular risk factors. To study the potential effects of relatively  diclofenac and highly specific  celecoxib COX-2 inhibitors on lipid profile and serum C-reactive protein in type 2 diabetes, whom have hyperlipidemia to be compared by their effects with normolipidemic patients. A total number of 34 type 2 diabetics (14 normolipidemics and 20 hyperlipidemics) treated with either diclofenac 100mg/day or celecoxib 200mg/day for eight weeks. Analysis  of results indicated that diclofenac increased serum triglycerides (TG) whereas; celecoxib group exerted a significant reduction in total cholesterol (TC), triglycerides (TG) levels in hyperlipidemic patients. Normolipidemic diabetics showed a significant elevation in serum total cholesterol, triglycerides and low density lipoprotein-cholesterol (LDL) with significant reduction in high density lipoprotein-cholesterol (HDL) in those treated with diclofenac , whilst those treated with celecoxib exhibited no modification of serum lipids. The results of the present study indicated that the net effect of treatment of hyperlipidemic type 2 diabetics by diclofenac was mostly qualitative as indicated by elevated TG/HDL ratio, to be a marker of atherogenic- small dense LDL particles in diabetics, whereas celecoxib exerted no such effect in this group but produced a beneficial reduction in LDL/HDL ratio. Meanwhile, diclofenac in  normolipidemic diabetics exert a significant qualitative and quantitative modulation of their serum lipid components presented by net elevation in both LDL/HDL and TG/HDL ratios.  As a conclusion the administration of relatively selective COX-2 inhibitors ( diclofenac ) to normolipidemic type 2 diabetics could adversely affect lipid metabolism by producing undesirable qualitative as well as , quantitative changes in serum lipid components, more than that observed in the hyperlipidemic diabetics.  Key Words: Diabetes, lipid profile, cox-2 selectivity